Ultra-high resolution mass spectrometry of physical speciation patterns of organic matter in fire-affected soils. (1st November 2018) - Jiménez-Morillo, Nicasio T.; González-Pérez, José A.; Almendros, Gonzalo; De la Rosa, José M.; Waggoner, Derek C.; Jordán, Antonio; Zavala, Lorena M.; González-Vila, Francisco J.; Hatcher, Patrick G.
Abstract: Fire is one of the most important modulating factors of the environment and the forest inducing chemical and biological changes on the most reactive soil component, the soil organic matter (SOM). Assuming the complex composition of the SOM, we used an ultra-high resolution mass spectrometry analysis technique to assess the chemical composition and fire-induced alterations in soil particle size fractions (coarse and fine) from a sandy soil in a Mediterranean oak forest at Doñana National Park (Southwest Spain). Electrospray ionization-Fourier transform ion cyclotron resonance mass spectrometry (ESI-FTICRMS) showed that the coarse fraction of soils not affected by fires consisted mainly of polyphenolic compounds consistent with little-transformed SOM and fresh biomass, whereas the fine fraction was enriched in protein and lipid like homologues suggesting microbially reworked SOM. In fire-affected SOM, the coarse fraction contained a high proportion of aromatic compounds, consistent with inputs of charred litter or in situ chemical transformation of the SOM. Analysis of the fine fraction revealed two differentiated chemical families pointing to the existence of two carbon pools; a native microbial-derived moiety composed of lipids and polypeptide compounds, and a secondary, pyrogenic or thermally-altered moiety rich in aromatic compounds. This work represents the first application of ultra-high resolution mass spectrometry to study the chemical composition of SOM in different particle size fractions. Graphical abstract: Highlights: Ultra-high resolution mass spectrometry informs on the maturity of SOM in soil particle size fractions. SOM in coarse fraction has a biomass character, whereas fine fractions display a humified character. SOM in fire-affected coarse fraction contain a high contribution of aromatic compounds. SOM in fire-affected coarse fraction shows reduction of external functional groups. SOM in fire-affected fine fraction have two distinct carbon pools; microbial-derived and fire-derived.